Una lluvia de males: el régimen de precipitaciones en la Costa Rica del "progreso". Trayectoria, representaciones sociales e impacto socioeconómico (1860-1940) - Goebel Mc Dermott, Anthony (2009)
This papers analyses the relationship between the evolution of rainfalls and economic and socioenvironmental dynamism in Costa Rica in a period of State-building process, the consolidation of global economic exchange, and the definition of new relations with the environment, all guided by the ?progress? ideology. Besides analyzing the real impact of rainfall, this essay studies the major social representations of rainfall and its characterization by a diversity of historical subjects.